2018
DOI: 10.1097/aln.0000000000002143
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Impact of Mechanical Power at High and Low Tidal Volumes in Experimental Mild Acute Respiratory Distress Syndrome

Abstract: Background The authors hypothesized that low tidal volume (VT) would minimize ventilator-induced lung injury regardless of the degree of mechanical power. The authors investigated the impact of power, obtained by different combinations of VT and respiratory rate (RR), on ventilator-induced lung injury in experimental mild acute respiratory distress syndrome (ARDS). Methods Forty Wistar rats received Escherichia coli lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 40 publications
2
58
0
1
Order By: Relevance
“…Recurrent delivery of tidal energy inflicts VILI when stress and strain exceed the limits of tissue tolerance. Experimental work linked mechanical power > 12 J/min to the development of VILI [18][19][20][21] and adverse outcome in clinical studies in adults [7,8,22]. To date, there are no pediatric studies that have examined such relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent delivery of tidal energy inflicts VILI when stress and strain exceed the limits of tissue tolerance. Experimental work linked mechanical power > 12 J/min to the development of VILI [18][19][20][21] and adverse outcome in clinical studies in adults [7,8,22]. To date, there are no pediatric studies that have examined such relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, driving pressure was not an independent factor associated with 28-day mortality in ventilated patients with severe pneumonia, but MP was an independent factor. In experimental mild ARDS of rats, even at low V T , high MP promoted VILI [27]. In a computational study, MP showed a strong correlation with the relative risk of death across all ranges of driving pressures and PEEP [28].…”
Section: Discussionmentioning
confidence: 92%
“…While input of cumulative total energy and total power have been experimentally demonstrated to be linked to VILI [3,14,15], exactly which delivered component or subcomponent of power best correlates with damage has not been clearly identified. For example, it might be argued that only energy that relates to driving pressure or total elastic pressure (the product of volume and absolute alveolar pressure, ΔP + PEEP) would best track stretch and VILI risk.…”
Section: Sub-components and Thresholds Of Tidal Energymentioning
confidence: 99%
“…Although total inflation power, i.e., the energy per cycle multiplied by ventilating frequency, has been causally linked to VILI risk [3], not all combinations of the three pressure components of energy and frequency that sum to the same total power value are equally hazardous. For injury to occur, a second requirement (apart from the raw power total) is a precondition; enough strain per cycle must be imposed to sufficiently distort lung parenchyma or disrupt vulnerable elements of the extracellular matrix that comprise the interdependent supporting framework for the alveolar network.…”
mentioning
confidence: 99%